1996
DOI: 10.1021/ac950764a
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sulfated Cyclodextrins to Chiral Separations by Capillary Zone Electrophoresis

Abstract: Mixtures of randomly substituted sulfated cyclodextrins (degree of substitution, approximately 7-10) were successfully used as chiral additives for the enantioseparation of 56 compounds of pharmaceutical interest, including anesthetics, antiarrhythmics, antidepressants, anticonvulsants, antihistamines, antihypertensives, antimalarials, relaxants, and bronchodilators. The separations were accomplished at pH 3.8, with the anode at the detector end of the column. Under these conditions, in which electroosmotic fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
137
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(141 citation statements)
references
References 32 publications
(32 reference statements)
1
137
0
3
Order By: Relevance
“…However, during the last decades the most important analytical applications of cyclodextrins and micellar media were focused on separation techniques, mostly HPLC or capillary zone electrophoresis (CZE) and their variants. In particular, the progress in chiral separation have been boosted by the use of cyclodextrins [85,119,120]. …”
Section: Analytical Applications Advantages Resulting From the Use Ofmentioning
confidence: 99%
“…However, during the last decades the most important analytical applications of cyclodextrins and micellar media were focused on separation techniques, mostly HPLC or capillary zone electrophoresis (CZE) and their variants. In particular, the progress in chiral separation have been boosted by the use of cyclodextrins [85,119,120]. …”
Section: Analytical Applications Advantages Resulting From the Use Ofmentioning
confidence: 99%
“…Entre os derivados carregados de CDs disponíveis comercialmente, destacam-se a β-CD carboxilada, a β-CD sulfobutiléter e a β-CD sulfatada. Essas CDs estão sendo cada vez mais citadas na literatura, em um grande número de separações quirais para compostos de diferentes classes 81,[84][85][86][87][88][89][90][91][92][93][94][95] . A separação de enantiômeros empregando os derivados de CDs depende não apenas do tipo de CD e de sua concentração, mas também de outras características como grau de substituição e posição em que os substituintes se encontram.…”
Section: Separação De Enantiômeros Por Ceunclassified
“…Among functionalized CDs, sulfated CDs are recognized as being the best effective selectors, especially when they were used in CE as chiral additives. [19][20][21][22] Theoretically, it is likely to be excellent if the sulfated CDs are used in HPLC or CEC for enantiomeric separation. Surprisingly, very few studies related to sulfated CDs used in HPLC and CEC have been reported.…”
Section: Introductionmentioning
confidence: 99%